2020
DOI: 10.1038/s41598-020-71989-6
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT analysis of dentinal microcracks on root canals filled with a bioceramic sealer and retreated with reciprocating instruments

Abstract: This study aimed to analyze the potential occurrence of dentinal defects after the removal of a root canal filling with two different sealers using Reciproc (RC) or Reciproc Blue (RB). The mesial roots of 60 mandibular molars with a Vertucci type IV configuration were selected. The samples were initially instrumented with Reciproc (R25) and then divided into the following four experimental groups according to the endodontic sealer and retreatment instrument (n = 15): BC Sealer/Reciproc (BCRC); BC Sealer/Recipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Studies revealed that dentinal microcracks formed when using PTR and RB during root canal retreatment [15,31], but limited evidence presented this phenomenon in WOG. At present, the formation and increased rate of new dentinal microcrack during retreatment procedure are still controversial [15,32,33]. Our results displayed that all three approaches produced microcracks in the root wall, which could be relevant to the increased heat production during retreatment due to the high-strength of iRoot SP and strong bond between iRoot SP and dentine.…”
Section: Discussionmentioning
confidence: 73%
“…Studies revealed that dentinal microcracks formed when using PTR and RB during root canal retreatment [15,31], but limited evidence presented this phenomenon in WOG. At present, the formation and increased rate of new dentinal microcrack during retreatment procedure are still controversial [15,32,33]. Our results displayed that all three approaches produced microcracks in the root wall, which could be relevant to the increased heat production during retreatment due to the high-strength of iRoot SP and strong bond between iRoot SP and dentine.…”
Section: Discussionmentioning
confidence: 73%
“…This is possible because the microscope performs several slices of the sample at depths of 20–30 µm [ 22 ], and overlaps them, providing a three-dimensional image that allows for seeing the path that the sealer has traveled inside the dentinal tubules. In other similar studies, different microscopic techniques have been used to assess tubular penetration, such as optical microscopy [ 23 ], scanning electron microscopy [ 24 ], or computerized microtomography [ 25 , 26 ]. However, these methods only study the surface of the samples and not their entire extension [ 15 ], thus providing limited information compared with confocal laser microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the removal of obturating material from canals filled with matched gutta-percha cone along with bioceramic-based sealer does not create dentinal microcracks. 35 Thus, the same obturating materials were used in this study to eliminate their impact on crack development.…”
Section: Discussionmentioning
confidence: 99%